Influenza A virus negative strand RNA is translated for CD8+ T cell immunosurveillance - Hickman, Heather D. (2018)
Probing the limits of CD8+ T cell immunosurveillance, we inserted the SIINFEKL peptide into influenza A virus (IAV)-negative strand gene segments. Although IAV genomic RNA is considered noncoding, there is a conserved, relatively long open reading frame present in segment 8, encoding a potential protein termed NEG8. The biosynthesis of NEG8 from IAV has yet to be demonstrated. Although we failed to detect NEG8 protein expression in IAV-infected mouse cells, cell surface Kb-SIINFEKL complexes are generated when SIINFEKL is genetically appended to the predicted C terminus of NEG8, as shown by activation of OT-I T cells in vitro and in vivo. Moreover, recombinant IAV encoding of SIINFEKL embedded in the negative strand of the neuraminidase-stalk coding sequence also activates OT-I T cells in mice. Together, our findings demonstrate both the translation of sequences on the negative strand of a single-stranded RNAvirus and its relevance in antiviral immunosurveillance.